(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Large variety of reinforcing materials emerged and have been developed for construction purposes, including: Metal strips, bar mats, Geotextile sheets, Geo Grids, and other reinforcing materials have emerged and been developed for construction applications. During the last few decades, reinforced soil technologies have been widely used in the construction of roads, bridges, and other structures (railway formation, highway embarkments, earth dams and retaining walls). Geo synthetics are frequently utilised in engineering practise as a reinforcing material to strengthen foundations, slopes, roads, pavements, crushed-stone columns, and other structures. Pavement is a hard crust that is built over natural dirt to provide a level driving surface for automobiles. Soil stabilisation in pavement construction is also concerned with the construction practise (highways, dams, bridges, and railway projects), and it demonstrates the numerous methods by which the stabilising responses of diverse soils can be found. This research discusses the features of soil eostnthetic intraction for various types of soils. Four different types of soils were utilised with geocomposit reinforced materials to conduct CBR tests to determine the density of soil samples and the mechanical strength of subgrade soil. These geo synthetic goods have aided engineers and builders in solving a variety of technical issues when the usage of traditional construction materials would be limited or prohibitively expensive.